Estudo comparativo entre MDF e MDP utilizados na indústria moveleira - Assis, Cristiano Prado [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Increasingly, the furniture market is competitive. The construction industry presents itself in growth, mainly due to the lines of existing incentives and tax credits established by the government, assisting the impulse to purchase real estate, building materials and furniture. Factors that promote and strengthen the sector's growth. With high demand from the furniture market, demand for higher quality and increasing technological advances, research is often undertaken in search of solutions for process improvement and product features, focusing on the production of materials less harmful to the environment, provision of raw press to lower cost, improve the production process and product development of cost-effective. This research focuses on the comparative study between two materials widely used in furniture manufacturing. MDF (Medium Density Fiberboard) and MDP (Medium Density Particleboard). The subject provides the focus in furniture production, presenting and comparing data collected from three companies producing panels between physical and mechanical characteristics of the materials, also presenting some of the main factors of influence on the quality of the panels, their features and applications on mobile. The study shows the high potential of using the MDP (Medium Density Particleboard) in furniture designs, as well as MDF (Medium Density Particleboard), favoring the final terms of the project , resulting in better utilization of each material , avoiding waste and increase unnecessary cost . Currently, several projects are developed in MDP and MDF furniture, where there is no relevance to their characteristics regarding their limitations. Many of these furnishings are designed without a specific study of the best use and positioning of each material, with better utilization , favoring collateral design , especially furniture designed exclusively for each environment . The lack of technical ...

Cada vez mais o mercado moveleiro encontra-se mais competitivo. O setor da construção civil apresenta-se em crescimento, principalmente devido às linhas de créditos existentes e incentivos fiscais estabelecidos pelo governo, auxiliando o impulso para compra de imóveis, materiais de construção e móveis. Fatores que favorecem e fortalecem o crescimento do setor. Com alta demanda do mercado mobiliário, maior exigência por qualidade e crescente avanço tecnológico, pesquisas são desenvolvidas frequentemente, em busca de soluções em melhoria de processo e características do produto, com foco na produção de materiais menos nocivos ao meio ambiente, disposição de matéria-prima de menor custo, melhorias no processo produtivo e desenvolvimento de produtos de alto custo-benefício. A presente pesquisa aborda o estudo comparativo entre dois materiais largamente utilizados na fabricação de móveis. O MDF (Medium Density Fiberboard) e MDP (Medium Density Particleboard). O assunto estabelece o foco na produção de móveis, apresentando e confrontando dados coletados, de três empresas produtoras dos painéis, entre características físicas e mecânicas dos materiais, apresentando também alguns dos principais fatores de influência na qualidade dos painéis, suas funcionalidades e aplicações em móveis. O estudo apresenta o alto potencial de utilização do MDP (Medium Density Particleboard) em projetos de móveis, bem como o MDF (Medium Density Particleboard), favorecendo as condições finais do projeto, resultando em melhor aproveitamento de cada material, evitando desperdício e aumento de custo desnecessário. Atualmente, são desenvolvidos diversos projetos de móveis em MDP e MDF, onde não há relevância sobre suas características em relação as suas limitações. Muitos desses móveis são projetados sem que haja um estudo específico do melhor uso e posicionamento de cada material,...
Keywords: Compensados de madeira; Chapa de madeira aglomerada; Indústria de móveis; Mobiliario; Wood furniture